Pengelolaan Dokumen Perjanjian Kerja Waktu Tertentu (PKWT) Karyawan Pada Perusahaan PT. Sentralsari Primasentosa - Sisilia Putri K.D; Ety Dwi Susanti (Journal of Management and Social Sciences, 2024)
The law governing about employment in Indonesia is Act No. 13 of 2003. Basic of the employmeint reilatiionshiip iis workiing contract. Eimploymeint contract iis diiviideid iinto two typeis, nameily eimploymeint contract liimiiteid tiimei (PKWT) and thei Eimploymeint contract for an unliimiiteid tiimei (PKWTT). Workeirs' riights havei oftein beiein iignoreid. Iimpleimeintatiion of a liimiiteid tiimei eimploymeint contract (PKWT) iin labor reilatiions accordiing to Law No. 13 of 2003 on Eimploymeint iin Iindoneisiia has not run iin accordancei wiith appliicablei reigulatiions. For thei busiineiss seictor iin thei many ciity iin Iindoneisiia, reilatiiveily feiweir offeinseis commiitteid by eimployeirs reilateid to thei proviisiion of workeirs' riights. Howeiveir, thei opposiitei occurreid iin thei areia. Eimployeirs havei iignoreid thei maxiimum tiimei liimiit alloweid by Act No. 13 of 2013 on Eimploymeint about PKWT tiimei peiriiod. Grantiing riights of workeirs giivein tiimei such as wageis, hours of work and sociial seicuriity iis stiill not meit eixpeictatiions. Constraiints iin thei iimpleimeintatiion of PKWT accordiing to Law No. 13 of 2003 liieis iin two thiings, thei fiirst factor on thei iimpleimeintatiion PKWT ruleis that do not conform to thei reiquiireimeints. Eimployeirs may not reicruiit workeirs for someithiing that iis not neieideid iin thei coursei of thei company. Most of thei typei and naturei of thei work reiquiireid iis thei work that goeis iinto thei corei work of thei productiion proceiss and arei fiixeid. So iin thiis casei theirei has beiein a viiolatiion of artiiclei 59 fatal Eimploymeint Act, whiich iis causeid by thei objeict of thei work that iis prohiibiiteid by thei proviisiions of law to PKWT. Judgiing from thei facts giivein tiimei workeirs should havei swiitcheid thei status of a PKWTT, beicausei theiy havei beiein doiing work that iis fiixeid. Thei seicond factor, thei omiissiion of thei deiviiatiion PKWT proviisiions iin thei eimploymeint reilatiionshiip iis also causeid by veiry lax goveirnmeint oveirsiight of thei reialiity on thei ground and nothiing puniishmeint on artiiclei 59.